Building cases for faculty development in e-learning: a design-based approach - Maria Ranieri; Juliana Raffaghelli; Francesca Pezzati (Firenze University Press, 2018)
This paper presents an integrated program of faculty development on e-learning, promoted by the University of Florence since 2016. It focuses on a specific pedagogical component of the program, i.e. case studies, and on the three-phase process of design, development and testing adopted to implement them. In the first phase exemplary cases were identified to develop a design format. The second phase aimed at checking this format against the best-performers' narratives of practice, and at designing the digital resource presenting the case. The third phase included user tests and an analysis of how professional learning was shaped in novices of e-learning. Through this process, the main elements influencing effective design and implementation of case studies for professional development on e-learning in the higher education were discovered. Costruire casi per lo sviluppo professionale degli accademici sull'e-learning: un approccio basato sul progetto Questo articolo presenta un programma integrato di sviluppo professionale sull'e-learning, promosso dall'Università di Firenze dal 2016. Si focalizza su una specifica componente pedagogica, vale a dire sui casi di studio, e sul processo di progettazione, sviluppo e test delle tre fasi adottate per realizzarli. Nella prima fase sono stati identificati casi esemplari per sviluppare un formato di progettazione. La seconda fase mirava a verificare questo formato rispetto alle narrazioni dei best-performers e a progettare le risorse digitali che presentano il caso. La terza fase comprendeva i test dell'utente e l'analisi di come l'apprendimento professionale fosse modellato nei novizi dell'e-learning. Attraverso questo processo, sono stati scoperti i principali elementi di efficacia per la progettazione e implementazione di case study per lo sviluppo professionale sull'e-learning in ambito universitario.